Design and application of an efficient cellulose-degrading microbial consortium and carboxymethyl cellulase production optimization - Zhang, Guoyan; Dong, Yuanjie (Frontiers in Microbiology, 2022)
Microbial consortia with high cellulase activities can speed up the composting of agricultural wastes with high cellulose contents and promote the beneficial utilization of agricultural wastes. In this paper, rabbit feces and sesame oil cake were used as feedstocks for compost production. Cellulose-degrading microbial strains were isolated from compost samples taken at the different composting stages and screened via Congo red staining and filter paper degradation test. Seven strains, Trichoderma reesei, Escherichia fergusonii, Proteus vulgaris, Aspergillus glaucus, Bacillus mycoides, Corynebacterium glutamicum, and Serratia marcescens, with high activities of carboxymethyl cellulase (CMCase), filter paper cellulase (FPase), and β-glucosidase (β-Gase) were identified and selected for consortium design. Six microbial consortia were designed with these strains. Compared with the other five consortia, consortium VI composed of all seven strains displayed the highest cellulase activities, 141.89, 104.56, and 131.18 U/ml of CMCase, FPase, and β-Gase, respectively. The single factor approach and response surface method were employed to optimize CMCase production of consortium VI. The optimized conditions were: culture time 4.25 d, culture temperature 35.5 °C, pH 6.6, and inoculum volume 5% (v/v). Under these optimized conditions, the CMCase activity of consortium VI was up to 170.83 U/ml. Fermentation experiment of rabbit feces was carried out by using the consortium VI cultured under the optimal conditions. It was found that the application effect was better than other treatments, and the fermentation efficiency and nutrient content of the pile were significantly improved. This study provides a basis for the design of microbial consortia for the composting of agricultural wastes with high cellulose contents and provides a support for beneficial utilization of agricultural wastes.